Curious George goes to a costume party - Rey, Margret; Shalleck, Alan J. (Boston : Houghton Mifflin, 2000)
While trying to find a costume for a party, George looks through Aunt Harriet's attic and makes a huge mass.
"Adapted from the Curious George film series."
Accelerated Reader AR
Keywords: Costume -- Juvenile fiction; Parties -- Fiction; Costume -- Fiction; Monkeys -- Fiction